2006
DOI: 10.1016/j.ijsolstr.2005.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of central bursting during axisymmetric cold extrusion of a metal alloy containing particles

Abstract: A simple cell model based damage dependent yield surface is used to model the effect of void nucleation and growth in an aluminum alloy during an axisymmetric cold extrusion process. Material parameters for characterization of the yield surface are determined through a physically consistent micromechanical cell modeling technique. The model can account for the behavior of a void containing a particle under severe compressive processing conditions. The formation of distinct, equally spaced, arrowhead shaped Ôce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…The results show that the damage zone significantly increases as the friction coefficient increases resulting in a more inhomogeneous deformation across the wire. Note that, in the problem of extrusion, a similar effect was observed by McVeigh and Liu (2006). Throughout the Fig.…”
Section: Friction-temperature Rise and Damage Relationshipsupporting
confidence: 67%
See 1 more Smart Citation
“…The results show that the damage zone significantly increases as the friction coefficient increases resulting in a more inhomogeneous deformation across the wire. Note that, in the problem of extrusion, a similar effect was observed by McVeigh and Liu (2006). Throughout the Fig.…”
Section: Friction-temperature Rise and Damage Relationshipsupporting
confidence: 67%
“…It was found that the internal or chevron cracks may occur when the inclusion size is larger than the critical inclusion size. McVeigh and Liu (2006) applied micromechanical cell modeling technique to predict the formation of central bursts during extrusion and edge cracking during rolling. They examined material hardening effects, surface friction and die geometry on the occurrence of central bursting.…”
Section: Introductionmentioning
confidence: 99%
“…Saanouni et al [10] applied continuum damage mechanics to thermo-elastoplastic finite element (FE) program and predicted crack formation in cold extrusion. McVeigh and Liu [11] used micro mechanical cell modeling technique and predicted the occurrence and position of chevron crack in extrusion and edge crack in rolling.…”
Section: Introductionmentioning
confidence: 99%
“…• The multiscale theory proposed and developed by Liu et al (see references mentioned above and also in [13][14][15][16][17]) is summarized in Section 3. The theory describes the multiscale character of damage and failure in random heterogeneous materials and gives rise to a set of equations that govern the physics of materials failure at each scale of interest.…”
Section: Introductionmentioning
confidence: 99%